Ireland : Fourth Review Under the Extended Arrangement and Request for Rephasing of the Arrangement: Staff Report; Letter of Intent; Memorandum of Economic and Financial Policies; Technical Memorandum of Understanding; Letter of Intent and Memorandum of Understanding on Specific Economic Policy Conditionality (College of Commissioners); Staff Supplement; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
The Irish authorities are adopting consolidation measures to meet the original fiscal targets as well as implementing structural reforms in the labor market and sheltered sectors to enhance competitiveness. Strengthened euro area support for Ireland's growth and debt sustainability would greatly reinforce prospects for Ireland to regain market access at an early stage given more adverse circumstances. Reports suggest that investors are differentiating Ireland based on its policy implementation track record and growth prospects. Vulnerabilities persist, however, as international demand for Irish bonds is sensitive to developments in the euro area.